Professional competency: Pre-service mathematics teachers’ understanding toward probability concept - Sitti Karimah Sulfiah; Yus Mochamad Cholily; Agus Subaidi (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2021)
The ability to understand mathematics is a faculty crucial to be possessed by pre-service teachers who will enter into the education sphere. It is one of the professional competencies essential for teachers since satisfactory lessons’ delivery engenders more comprehensible instruction in teachers’ students. Qualitative research employs a descriptive approach relevant to the research purpose, describing mathematics pre-service teachers’ professional competency of understanding the concept toward probability observed based on mathematical abilities; advanced, intermediate, and basic mathematics ability. The subjects are three pre-service teachers having passed discrete mathematics course in a college in Madura. The criteria to select the subjects are the GPA (Grade-point Average) of the last semester and information from the lecturer.  It is because unlikely to administer the test due to online learning applied at the college. Findings indicated that the subject with advanced mathematics ability could meet individual concepts, relate concepts and connect concepts with the operations. The subject with intermediate mathematics ability could meet individual concepts, but could not relate to some concepts. However,  he could connect concepts with the operations. The subject with basic mathematics ability could not meet individual concepts, relate concepts, and connect concepts with the operations. In terms of the advancement indicator of understanding the concept, the subjects have not attained it since they have not apprehended concept definition well, particularly the probability concept, although the subject with advanced mathematics ability was procedurally prodigious.